VIABILITY AND PLASMA MEMBRANE INTEGRITY OF THE SPOTTED BUFFALO EPIDIDYMAL SPERMATOZOA AFTER THAWING WITH THE ADDITION OF DEXTROSE INTO THE EXTENDER - YULNAWATI YULNAWATI; H. MAHESHWARI; HERDIS; M. RIZAL (BIOTROPIA, 2009)
The objective of this study was to obtain the viability and plasma membrane integrity of the spotted buffalo epididymal sperm after addition of dextrose into AndromedÒ extender.  Spermatozoa that have been collected from cauda epididymis were diluted with AndromedÒ extender as control (K) and AndromedÒ + 0.2% dextrose (P1) and AndromedÒ + 0.4% dextrose (P2) as treatments.  The results showed that the quality of epididymal spermatozoa decreased during cryopreservation process.  The percentage of motility after thawing in P1 (46%) and P2 (46.67%) were significantly higher (P